Perancangan Dokumen Sistem Manajemen Mutu ISO 9001: 2015 di PT. X - The Meishia Rosari Marianca; Togar Wiliater Soaloon Panjaitan (Jurnal Titra, 2023)
Efforts to handle waste or garbage are not only the responsibility of the government, but also require the support of many parties, such as private waste processing companies. PT. X is a private company engaged in waste processing. This company wants to continue to innovate in developing waste processing machines made by the nation’s children. To support the achievementof these goals, the company wishes to improve good quality performance in the company. One of the way to improve this quality is a plan to adopt a quality management standard in the form of ISO 9001 which has not been owned yet. This study aims to prepare companies to adopt ISO 9001: 2015. The initial GAP analysis results show that PT. X has not had the documents related to ISO 9001: 2015 yet. After designing and developing the fulfillment of the five clauses, named clauses four to eight, the final GAP analysis will be able to be obtained. It can be said that PT. X is able to reach the target. It is the 100% fulfillment of the total five clauses of ISO 9001: 2015 which are targeted to be met.